Family-Based Character Education: Parental Practices And Strategies in Forming Adolescent Morals in Rural Central Kalimantan - Wahyu Riswanto; Hamdanah; Saudah (Institut Agama Islam An-Nawawi Purworejo, 2025)
Character education in the family plays an important role in the formation of children's morals, especially in rural areas that face limited access to formal education and technology. This article aims to explore the practices and strategies of parents in forming the morals of adolescents in Pembuang Hulu, Seruyan Regency, Central Kalimantan. This study uses a qualitative approach with in-depth interviews with five parents who have adolescents. The results show that parents in Pembuang Hulu rely on habituation methods, such as inviting children to study the Koran and pray in congregation, to form the character of adolescents. In addition, parental role models and attention to supervising children, both at home and in their social interactions, have proven effective in forming morals. However, the main challenges faced are the influence of the less supportive external environment and the use of technology, such as mobile phones and online games. Nevertheless, the active role of parents in supervising their children's development is very important in overcoming these challenges. This study makes an important contribution to the understanding of the role of families in children's character education in rural areas and encourages collaboration between families and educational institutions to create an environment that supports character education.